2003
DOI: 10.1001/archinte.163.22.2759
|View full text |Cite
|
Sign up to set email alerts
|

Venous Thrombosis After Long-haul Flights

Abstract: Long-haul flights of 8 hours and longer double the risk for isolated calf muscle venous thrombosis. This translates into an increased risk for deep venous thrombosis as well. In our study, flight-associated thrombosis occurred exclusively in passengers with well-established risk factors for venous thrombosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(62 citation statements)
references
References 21 publications
2
56
0
3
Order By: Relevance
“…10 In a trial on flight-associated thrombosis, we could show an incidence of 10/1000 asymptomatic ICMVT in a month in a cohort of nontraveling controls performing compression ultrasound at inclusion and 3 to 4 weeks after. 11 We conclude that the incidence of ICMVT is 100 times higher than it is known for symptomatic DVT. 12,13 We assume that most of these small thrombi disappear completely via natural lysis, but a fraction will develop as symptomatic with a potential of progression.…”
Section: Discussionmentioning
confidence: 66%
“…10 In a trial on flight-associated thrombosis, we could show an incidence of 10/1000 asymptomatic ICMVT in a month in a cohort of nontraveling controls performing compression ultrasound at inclusion and 3 to 4 weeks after. 11 We conclude that the incidence of ICMVT is 100 times higher than it is known for symptomatic DVT. 12,13 We assume that most of these small thrombi disappear completely via natural lysis, but a fraction will develop as symptomatic with a potential of progression.…”
Section: Discussionmentioning
confidence: 66%
“…Air travel of long duration is reportedly associated with a hypercoaguable state in normal individuals. Several studies suggest that the mild hypobaric hypoxia of commercial air travel is associated with a hypercoaguable state on long flights; this was noted in healthy volunteers with elevated risk factors such as age, high body mass index [16], use of oral contraceptives, and factor V Leiden mutation [15]. To determine if tourniquet-induced muscle ischemic injury represents a similar risk factor, we measured coagulation parameters and found that 2 h of tourniquet-induced ischemia followed by 6 h exposure to HB or NB conditions did not affect standard plasma assays of coagulation (PT, aPTT) or any TEG parameters.…”
Section: Discussionmentioning
confidence: 99%
“…We therefore also assessed muscle myeloperoxidase (MPO) activity as an index of oxidative stress and PMN infiltration into muscle. Further, we measured alterations in coagulation parameters as air travel has been associated with a hypercoaguable state in healthy volunteers with risk factors, such as use of oral contraceptives, factor V Leiden mutation [15], advanced age, or high body mass index [16], and may pose a similar risk to trauma patients.…”
Section: Introductionmentioning
confidence: 99%
“…The risk of PE post air travel is 0.5/1 9 10 6 on the day of landing [5,6] and rises to 27/1 9 10 6 VTE (DVT or PE) during the first 14 days after landing [9]. Fatal PE was not observed in over 1 million passengers of transatlantic flights or in any of the 1341 patients diagnosed with PE shortly after landing [7].…”
Section: Epidemiologymentioning
confidence: 99%